THE EFFECT OF FRYING TEMPERATURE AND TIME IN VACUUM FRYING MACHINE ON THE IMPROVEMENT OF THE QUALITY OF APPLE CRISPS - Nely Ana Mufarida; Asroful Abidin; Fitriana Fitriana (MULTITEK INDONESIA, 2021)
The frying temperature in the frying process using a vacuum frying machine can be designed according to your needs. Usually used for frying at low temperatures so that damage to aroma and taste can be avoided. The purpose of this study was to analyze the effect of temperature and frying time on a vacuum frying machine on improving the quality of apple chips so that apple chip products can be obtained according to consumer desires. The temperatures used for frying are 50, 55, and 60oC with time variations of 40, 50, and 60 minutes. This aims to avoid changes in color and taste to obtain optimal quality apple chips. The water content of fried apples is 85% - 86.5%. The maximum capacity of the frying tube is 2 kg with a requirement of 12 liters of cooking oil. The main processed ingredients used in this study were manalagi varieties of apples. The resulting chips have a delicious, sweet, crispy texture, and have a yellow color. The higher the temperature and the longer the frying time, the air content tends to decrease. This is caused by higher heat which causes greater evaporation of air from inside the material. The results of the fried ingredients are more crunchy because evaporation at a low boiling point allows more air content to evaporate.